Ligand-based discovery of novel N-arylpyrrole derivatives as broad-spectrum antimicrobial agents with antibiofilm and anti-virulence activity - Basma M. Qandeel; Samar Mowafy; Mohamed F. El-Badawy; Nahla A. Farag; Galal Yahya; Khaled Abouzid (Journal of Enzyme Inhibition and Medicinal Chemistry, 2025)
The escalating threat of antimicrobial resistance calls for novel therapeutic agents. This study employed a ligand-based design approach to develop three series of N-arylpyrrole derivatives (Va–e, VIa–e, and VIIa–e), refined through molecular modeling. Synthesized compounds were evaluated against ESKAPE pathogens, MRSA, and Mycobacterium phlei. Series Va–e showed the most promise, with compounds Vb, Vc, and Ve outperforming levofloxacin against MRSA (MIC = 4 μg/mL vs. 8 μg/mL). Vc also exhibited activity against E. coli, K. pneumoniae, and A. baumannii, and showed significant inhibition against M. phlei (MIC = 8 μg/mL). Compounds were evaluated for antibiofilm and antivirulence properties, targeting resistance mechanisms linked to infection persistence and dissemination. Most exhibited broad-spectrum biofilm inhibition and antivirulence activity. Cytotoxicity studies revealed selectivity for bacterial cells. ADMET studies supported drug-like properties. Docking studies suggested UPPP inhibition as the potential mechanism. SAR analysis was conducted to support future optimizations.